LoRaWAN Technology in Irrigation Channels in Batu Indonesia - Puput Dani Prasetyo Adi; Akio Kitagawa; Dwi Arman Prasetya; Rahman Arifuddin; Stanislaus Yoseph (Universitas Ahmad Dahlan, 2021)
Currently, agricultural technology or Farming development is increasingly sophisticated by applying LoRaWAN-based IoT technology, ignoring quality agricultural products. LoRaWAN used in this research uses Long-Range Frequency 915 MHz and 920 MHz. The case study in this research is a case of river water quality that enters agricultural land or irrigation in Temas, Batu City, where the river water has been contaminated by household waste. The prototype installed on this farm uses an Arduino and Dragino LoRa 915 MHz microcontroller as transceivers and input and output devices consisting of ultrasonic sensors and water pH sensors, and outputs such as Solenoid valves mounted on tub one and tub 2. In contrast, tub 3 is a unique tub for distributing water to agricultural land with normal water pH quality. In this research, real-time monitoring, especially on the conditions of water turbidity, water pH, and water level.